Effect of Peganum Harmala Methanol Extract on Liver and Kidney of Mice Administered MTX Drug - Diwan, Saddam Yahya (Al-Nahrain Journal of Science, 2013)
This research was designed to evaluate the role of Peganum harmala methanol seed extract in amelioration the biochemical side effect of liver and kidney in mice administered MTX drug. The biochemical detections for both kidney functions (urea and creatinine) and liver enzymes (GOT, GPT and ALP) were investigated. This detection was carried on 30 mice through two stages. In stage Ι, two doses (75 and 100) mg/kg of P. harmala seed extract and a single dose of MTX 50 mg/kg were used. The tested materials were dosed as a single dose (0.1 ml) per a day for 6 days, and then mice were sacrificed on day 7 for subsequent assesments. In stage ІІ, interaction between MTX drug and two doses of extract were carried out. Mice were given MTX dose on day one, while the extract was given in day two till day 6, then mice were sacrificed on day 7 for laboratory evaluation. Results revealed that mice treated MTX showed a significant increase in liver enzymes and kidney function; in contrast, biochemical parameters demonstrated the amelioration effect of extract through decreasing these parameters.